Confined Growth of NiAl-Layered Double Hydroxide Nanoparticles Within Alginate Gel: Influence on Electrochemical Properties - Prevot, Vanessa; Touati, Souad; Mousty, Christine (Frontiers in Chemistry, 2020)
NiAl Layered Double Hydroxide (LDH) alginate bionanocomposites were synthesized by confined coprecipitation within alginate beads. The NiAl based bionanocomposites were prepared either by impregnation by divalent and trivalent metal cations of pre-formed calcium cross-linked alginate beads or by using the metal cations (Ni2+, Al3+) as crosslinking cationic agents for the biopolymer network. The impregnation step was systematically followed by a soaking in NaOH solution to induce the LDH coprecipitation. Powder x-ray diffraction (PXRD), infrared spectroscopy (FTIR), energy dispersive X-ray analysis (EDX), thermogravimetry analysis (TGA), electron microscopies (SEM and TEM) confirmed the biotemplated coprecipitation of LDH nanoparticles ranging from 75 to 150 nm for both strategies. The drying of the LDH@alginate beads by supercritical CO2 drying process led to porous bionanocomposite aerogels when Ca2+ cross-linked alginate beads were used. Such confined preparation of NiAl LDH was extended to bionanocomposite films leading to similar results. The permeability and the electrochemical behavior of these NiAl@alginate bionanocomposites, as thin films coated on indium tin oxide (ITO) electrodes, were investigated by cyclic voltammetry, demonstrating an efficient diffusion of the K4Fe(CN)6 redox probe through the LDH@alginate based films and the improvement of the electrochemical accessibility of the Ni sites.